VISIÓN DIACRÓNICA DEL TRATAMIENTO DIDÁCTICO DEL LÉXICO EN LA FORMACIÓN INICIAL DE PROFESORES DE ESPAÑOL-LITERATURA - Grechel Calzadilla Vega; Marlen Aurora Domínguez Hernández; Roberto Fernando Valledor Estevill (University of Las Tunas, 2018)
Este artículo presenta resultados del proceso de investigación doctoral de la autora principal, relacionado con la disponibilidad léxica de profesores de EspañolLiteratura en formación inicial. Como parte de él se constataron insuficiencias en la disponibilidad léxica de dichos sujetos que atentan contra la calidad de su discurso en contextos de interacción sociocomunicativa profesional e interpersonal. Ello se contradice con lo que, al respecto, exige el modelo de este profesional una vez egresado. Por tanto, el presente artículo tiene como objetivo profundizar en el tratamiento didáctico ofrecido al léxico en el proceso de formación de profesores en esta especialidad, para conocer las particularidades de su evolución histórica y proyectar acciones futuras que contribuyan a erradicar las insuficiencias antes mencionadas. Para realizarlo se utilizaron métodos del nivel teórico y empírico, se establecieron los criterios y etapas para la periodización. ABSTRACT This article shows the results of the principal author's doctorate research process. It is related to the lexical availability of teachers of Spanish and Literature in initial formation. To start from the insufficiencies detected referring to the lexical performance, it was carried out a historical contextual analysis of its treatment in the teaching learning process of Spanish Lexis during the theoretical search about the causes of the scientific problem identified in the research. It was used theoretical and empirical methods, such as the historical-logical, analysissynthesis, induction-deduction, analysis and sources' criticism, as well as interviews, surveys, statements and the analysis of the products of the pedagogical process, respectively. The criterions for the analysis were established and two stages for the periodization were determined. The analysis carried out allowed corroborating the needs to offer a didactic treatment for the lexicon in the teaching learning process of Spanish Lexis that allows counting on planning, systematic, procedural and scientific orientation. This favors to increase the lexical availability and, in consequence, the quality of the speech of teachers of Spanish-Literature in initial formation in the contexts of the interpersonal and professional communicative interaction. KEY WORDS: Lexical availability, lexicon, vocabulary.